The Development of Teaching Materials Based on Local Assistance in the Appreciation Materials of Indonesian Education Students UHKBPNP - Monalisa Frince S; Marlina A Tambunan (BIRCU, 2020)
This study aims to determine: (1) the development of teaching materials based on local wisdom on prose appreciation materials, (2) the appropriateness of teaching materials based on local wisdom on prose appreciation materials. This type of research is research and development based on the Borg and Gall development model. The trial subjects consisted of material experts, design experts, Indonesian language education lecturers, and Indonesian language education students. Data about the quality of this product were collected through questionnaires and tests to appreciate prose by writing short stories. The results of this study indicate that: (1) material validation includes content eligibility with an average of 93.75% on very good criteria, presentation feasibility with an average of 91.34% on very good criteria, language eligibility with an average of 95, 19% on very good criteria, (2) validation of design experts with an average of 92.08% on very good criteria, (3) individual trials with an average of 82.50% with very good criteria, (4) small group trials with an average of 90 , 27% with very good criteria, and (5) limited field group test with an average of 94.02% with very good criteria. Thus, the module based on local wisdom on prose appreciation material that has been developed is suitable for use as a learning resource.